Cross-reactivity influences changes in human influenza A virus and Epstein Barr virus specific CD8 memory T cell receptor alpha and beta repertoires between young and old - Clark, Fransenio; Gil, Anna; Thapa, Ishwor; Aslan, Nuray; Ghersi, Dario; Selin, Liisa K. (Frontiers in Immunology, 2023)
Older people have difficulty controlling infection with common viruses such as IAV, RNA virus which causes recurrent infections due to a high rate of genetic mutation, and EBV, DNA virus which persists in B cells for life in the 95% of people that become acutely infected. We questioned whether changes in epitope-specific memory CD8 TCR repertoires to these two common viruses could occur with increasing age and contribute to waning immunity. We compared CD8 memory TCR alpha and beta repertoires in two HLA-A2+ age groups, young donors (YSP) and older donors (OSP) to three immunodominant epitopes known to be cross-reactive, IAV-M158-66 (IAV-M1), EBV-BMLF1280-288 (EBV-BM), and EBV-BR109-117 (EBV-BR). We, therefore, also designed these studies to examine if TCR cross-reactivity could contribute to changes in repertoire with increasing age. TCR high throughput sequencing showed a significant difference in the pattern of TRBV usage between YSP and OSP. However, there were many more differences in AV and AJ usage, between the age groups suggesting that changes in TCR usage may play a greater role in evolution of the TCR repertoire emphasizing the importance of studying TRAV repertoires. With increasing age there was a preferential retention of TCR for all three epitopes with features in their complementarity-determining region (CDR3) that increased their ease of generation, and their cross-reactive potential. YSP and OSP differed in the patterns of AV/AJ and BV/BJ pairings and usage of dominant CDR3 motifs specific to all three epitopes. Both YSP and OSP had cross-reactive responses between these 3 epitopes, which were unique and differed from the cognate responses having features that suggested they could interact with either ligand. There was an increased tendency for the classic IAV-M1 specific clone BV19-IRSS-JB2.7/AV27-CAGGGSQGNLIF-AJ42 to appear among the cross-reactive clones, suggesting that the dominance of this clone may relate to its cross-reactivity with EBV. These results suggest that although OSP and YSP retain classic TCR features for each epitope their repertoires are gradually changing with age, maintaining TCRs that are cross-reactive between these two common human viruses, one with recurrent infections and the other a persistent virus which frequently reactivates.